Safety of antiepileptic drugs in children and young people: a prospective cohort study - Egunsola, Oluwaseun; Choonara, Imti; Sammons, Helen M.; Whitehouse, William P. (Elsevier, 2018)
Purpose: This study aims to describe the incidence of adverse drug reactions (ADRs) in children receiving antiepileptic drugs (AEDs) and compare ADRs to the individual drugs when given as monotherapy.